Inovação sociotécnica e multinível em energia eólica - Rodrigues, Beatriz da Silva (2022)
The decline of oil reserves, increase in their values (from the supply and demand process), environmental pollution and the context of climate change in the world, have caused constant concerns among nations. Thus, from the context briefly presented, it will be evaluated from a multilevel analysis, which mainly highlights the process of influences suffered by innovation in different directions, especially from three levels; Micro level, where radical innovations emerge; meso level, corresponding to socio-technical regimes; Finally, the macro level, in which it is characterized as the environment that provide structural changes as a whole in society. In view of the above, the purpose of this work was to answer the following question: What are the main gaps and notes of studies on wind energy from a socio-technical approach and a multilevel perspective of innovation? Regarding the methodology In order to carry out a systematic literature review, it was necessary to follow some essential steps, namely: Formulation of the research question; Locate the studies; Selection and evaluation of studies; Analysis and synthesis; Reporting and use of search results. Finally, as a result at the Micro level, the clear presence of multi-actors who drive initiatives for the emergence of niches. At the Meso level, it is evident that initiatives from different companies, research and work in similar directions are started. And the Macro level, which shows the windows of opportunity that innovation suffers depending on the system, among its characteristics found, the presence of governments and the support of low carbon structures was evident.